Adaptation of the Islamic Guidance and Counseling Curriculum: Cultural Integration and Da'wah - Budiyono, Alief; Azizah, Nur; Nugroho, Adhitya Ridwan Budhi Prasetyo; Sophian, Muhamad (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
The Islamic Guidance and Counseling Study Program implements the MBKM curriculum by integrating inclusive and contextual cultural and da'wah values, where the MBKM policy demands adaptive and contextual curriculum innovation. The differences in cultural backgrounds between UIN Prof. K.H. Saifuddin Zuhri Purwokerto (Javanese culture) and UIN Sultan Aji Muhammad Idris Samarinda (Dayak and Malay culture) are an opportunity to develop a curriculum based on cultural integration and da'wah. This study aims to explore the adaptation of the MBKM curriculum of the Islamic Guidance and Counseling (BKI) study program based on cultural integration and da'wah. This study uses a qualitative approach with a phenomenological method. Data were collected through in-depth interviews, observations, and documentation studies of study program managers at both institutions. The results of the study indicate that the implementation of the MBKM curriculum based on cultural integration and da'wah in the BKI Study Program at UIN Saizu Purwokerto and UINSI Samarinda can broaden students' horizons in understanding the socio-cultural dynamics of society. This curriculum encourages students to be more sensitive to the local context in counseling and da'wah practices, and to develop an inclusive and contextual approach. Cultural integration in the curriculum not only improves students' cross-cultural competence but also strengthens local wisdom-based preaching strategies that are relevant to the spirit of MBKM.